Since you asked: Arizona veterans share their memories (Cactus Shadows High School, 2005)
Description Not Provided

Hopi (Abrams, Abradale Press/H.N. Abrams, Rio Nuevo Publishers, 2008)
Featuring a special section devoted to the Hopi's superb crafts--pottery, weaving, jewelry, and painting--an exploration of significant aspects of traditional Hopi life consists of six photo essays: Ceremonies, Corn, Daily Life, Wedding Ceremonies, Eagle Ceremony, and Pilgrimage.
Warning --, Traditional vs. progressive --, The ceremonial year --, Tasks and tiruals --, Pasts --, Among the spirits --, The land.

Writers at work: the Paris review interviews, ninth series (Viking, Penguin Books, 1985)
Description Not Provided
Samuel Beckett , P. L. Travers , Wallace Stegner , Octavio Paz , Walker Percy , Doris Lessing , William Kennedy , Maya Angelou , Harold Bloom , Tom Wolfe , Mario Vargas Llosa , Tom Stoppard.

Love medicine (Bantam Books, Perennial, Harper Perennial, Holt, Rinehart, and Winston, HarperPerennial Modern Classics, 2009)
The first book in the tetralogy that includes The Beet Queen, Tracks, and The Bingo Palace follows the lives of two native American families and is enhanced by four previously unpublished chapters. The first book in Louise Erdrich's Native American series, which also includes The Beet Queen, Tracks, and The Bingo Palace, Love Medicine tells the story of two families--the Kashpaws and the Lamartines. Now resequenced by the author with the addition of never-before-published chapters, this is a publishing event equivalent to the presentation of a new and definitive text. Written in Erdrich's uniquely poetic, powerful style, Love Medicine springs to raging life: a multigenerational portrait of new truths and secrets whose time has come, of strong men and women caught in an unforgettable drama of anger, desire, and the healing power that is Love Medicine. Discover the writer whom Philp Roth called "the most interesting new American novelist to have appeared in years" all over again.

Apache voices: their stories of survival as told to Eve Ball (University of New Mexico Press, 2003)
Description Not Provided
Lozen , Tres castillos , Captives , Geronimo and the Arroyo fight , Streeter , Geronimo's surrender , Geronimo and Naiche , The impostors , Eskiminzin , The Apache Kid , Massai , Gordo and Juh , Gold and treasure , Cadette , Bosque redondo , The Mescalero Reservation , The Apaches and Comanches , Comanche stories , Victorio and the Mescaleros , The Battle of Round Mountain , Billy the Kid , The Apache general store , The Apache pharmacy , Medicine men and women , Weapons and warfare , Bear tales and other animal stories , Eve Ball.

The power of myth (Anchor Books, Doubleday, 1991)
The noted mythologist discusses the relationship of ancient myths to modern life, including discussions of recent heros, tales of love and marriage, the power of myth, and mythic themes
Editor's Note ix --, I Myth and the Modern World 1 --, II Journey Inward 44 --, III First Storytellers 86 --, IV Sacrifice and Bliss 113 --, V Hero's Adventure 151 --, VI Gift of the Goddess 207 --, VII Tales of Love and Marriage 231 --, VIII Masks of Eternity 258.

This I believe: the personal philosophies of remarkable men and women (Book discussion guides, ,, 2006)
This I Believe features eighty Americans-from the famous to the unknown, completing the thought that the book's title begins. Each piece compels readers to rethink not only how they have arrived at their own personal beliefs but also the extent to which they share them with others.Featuring many renowned contributors and essays by some not-so-famous people: a Brooklyn lawyer; a part-time hospital clerk in Rehoboth, Massachusetts; a woman who sells yellow pages advertising in Fort Worth, Texas; and a man who serves on Rhode Island's parole board.The result is a stirring and provocative trip inside the minds and hearts of a diverse group of people whose beliefs and the incredibly varied ways in which they choose to express them reveal the American spirit at its best.
Foreword / Studs Terkel , Introduction / Jay Allison , Be cool to the pizza dude / Sarah Adams , Leaving identity issues to other folks / Phyllis Allen , In giving I connect with others / Isabel Allende , Remembering all the boys / Elvia Bautista , The mountain disappears / Leonard Bernstein , How is it possible to believe in God? / William F. Buckley, Jr. , The fellowship of the world / Niven Busch , There is no job more important than parenting / Benjamin Carson , A journey toward acceptance and love / Greg Chapman , A shared moment of trust / Warren Christopher , The hardest work you will ever do / Mary Cook , Good can be as communicable as evil / Norman Corwin , A daily walk just to listen / Susan Cosio , The elusive yet holy core / Kathy Dahlen , My father's evening star / William O. Douglas , An honest doubter: Have I learned anything important since I was sixteen? / Elizabeth Deutsch Earle , An ideal of service to our fellow man / Albert Einstein , The power and mystery of naming things / Eve Ensler , A goal of service to humankind / Anthony Fauci , The God who embraced me / John W. Fountain , Unleashing the power of creativity / Bill Gates , The people who love you when no one else will / Cecile Gilmer , The willingness to work for solutions / Newt Gingrich , The connection between strangers / Miles Goodwin , An athlete of God / Martha Graham , Seeing in beautiful, precise pictures / Temple Grandin , Disrupting my comfort zone / Brian Grazer , Science nourishes the mind and the sould / Brian Greene , In praise of the "Wobblies" / Ted Gup , The power of presence / Debbie Hall , A grown-up Barbie / Jane Hamill , Happy talk / Oscar Hammerstein II , Natural links in a long chain of being / Victor Hanson , Talking with the sun / Joy Harjo , A morning prayer in a little church / Helen Hayes , Our noble, essential decency / Robert A. Heinlein , A new birth of freedom / Maximillan Hodder , The benefits of restlessness and jagged edges / Kay Redfield Jamison , There is no God / Penn Jillette , A duty to heal / Pius Kamau , Living life with "Grace and elegant treeness" / Ruth Kamps , The light of a brighter day / Helen Keller , The bright lights of freedom / Harold Hongju Koh , The power of love to transform and heal / Jackie Lantry , The power of mysteries / Alan Lightman , Life grows in the soil of time / Thomas Mann , Why I close my restaurant / George Mardikian , The virtues of the quiet hero / John McCain , The joy and enthusiasm of reading / Rick Moody , There is such a thing as truth / Errol Morris , The rule of law / Michael Mullane , Getting angry can be a good thing / Cecilia Muñoz , Mysterious connections that link us together / Azar Nafisi , The making of poems / Gregory Orr , We are each other's business / Eboo Patel , The 50-percent theory of life / Steve Porter , The America I believe in / Colin Powell , The real consequences of justice / Frederic Reamer , There is more to life than my life / Jamaica Ritcher , Tomorrow will be a better day / Josh Rittenberg , Free minds and hearts at work / Jackie Robinson , Growth that starts from thinking / Eleanor Roosevelt , The artistry in hidden talents / Mel Rusnov , My fellow worms / Carl Sandburg , When children are wanted / Margaret Sanger , Jazz is the sound of God laughing / Colleen Shaddox , There is no such thing as too much barbecue / Jason Sheehan , The people have spoken / Mark shields , Everything potent is dangerous / Wallace Stegner , A balance between nature and nurture / Gloria Steinem , Life, liberty, and the pursuit of happiness / Andrew Sullivan , Always go to the funeral / Deirdre Sullivan , Finding prosperity by feeding monkeys / Harold Taw , I agree with a pagan / Arnold Toynbee , Testing the limits of what I know and feel / John Updike , How do you believe in a mystery? / Loudon Wainwright III , Creative solutions to life's challenges / Frank X. Walker , Goodness doesn't just happen / Rebecca West , When ordinary people achieve extraordinary things / Jody Williams , Afterword: The history of This I Believe: The power of an idea / Dan Gediman , Appendix A: Introduction to the 1950s This I Believe radio series / Edward R. Murrow , Appendix B: How to write your own This I Believe essay , Appendix C: How to use This I Believe in your community , Acknowledgments.

Let's spend the night together: backstage secrets of rock muses and supergroupies (Chicago Review Press, 2007)
Presents biographies of twenty-four rock groupies in their own words, including Tura Satana, Miss Mercy, Cynthia Plaster Caster, and Miss B.
Tura Satana : Miss Japan Beautiful and the King , Cherry Vanilla : the happiest broken heart , Gail Zappa : love at first sight , My Lady d'Arbanville , The elusive Miss James , Cynthia Plaster Caster : kicks , Dee Dee Keel : hey little girl, you wanna come on the bus? , Miss Mercy's blues : shock treatment , Michele Overman : love in her eyes and flowers in her hair , Cassandra : the virgin groupie , Lori Lightning : absolute beginners , Sweet Connie : there's only one way to rock , Gayle O'Connor : crazy, crazy nights , Margaret Moser and the Texas Blondes : slow dazzle , Pleasant Gehman : flesh for fantasy , A chat with Bebe Buell , Patti and Lisa : dangerous but worth the risk , Rebecca Bonyadi : come as you are , Pleather : celebrity skin , Lexa Vonn and the Plastics : user friendly , Sarah Madison : miss you in a heartbeat , Tina King : in so deep , Amanda Milius : let me stand next to your flower , Static Beth : size queen of the stars , Epilogue : Cameron Crowe : almost famous.

The wisdom of Sundays: life-changing insights from Super Soul conversations (Macmillan Audio, Flatiron Books, 2017)
Moments of inspiration from the three-time Emmy Award-winning Super Soul Sunday. Each chapter represents a powerful step in Oprah's own spiritual journey and is introduced with a personal essay by Oprah herself. Visionaries like Tony Robbins, Arianna Huffington, and Shonda Rhimes share their lessons in finding purpose. World-renowned teachers like Eckhart Tolle, Marianne Williamson, and Wayne Dyer explain our complex relationship with the ego and the healing powers of love and connection. And best-selling writers like Cheryl Strayed, Elizabeth Gilbert, and Elizabeth Lesser explore forgiveness and letting go. Paired with more than 100 beautiful photographs, including many from Oprah's private property in California, where episodes of Super Soul Sunday are filmed.
Awakening , Intention , Mindfulness , Spiritual GPS , Ego , Forgiveness , Broken open , Grace and gratitude , Fulfillment , Love and connection.

Immaculate deception II: myth, magic & birth (Celestial Arts, 1992)
Description Not Provided

Son of a wanted man (Louis L'Amour collection, ,, 1984)
Mike Bastian must decide whether he will take over his fathers gang or not, but he finds himself caught between jealous gang members, his growing love for an innocent girl, and the relentless pursuit of two lawmen.

Transgender voices: beyond women and men (University Press of New England, 2008)
Description Not Provided
The social construction of biological facts , Self-definition : birth through adolescence , Constructing the self : options and challenges , Coming out to community, family, and work , Gender policing , Inner turmoil and moving toward acceptance , Epilogue: Gender liberation.

Slaughterhouse-five, or, the children's crusade: a duty-dance with death (Dell, Blackstone Audio, Delacorte Press, Listen for Pleasure, Delacorte Press/Seymour Lawrence, HarperCollins, G.K. Hall, Caedmon/HarperCollinsPublishers, Dell Pub, 2009)
From the Publisher: Kurt Vonnegut's absurdist classic Slaughterhouse-Five introduces us to Billy Pilgrim, a man who becomes 'unstuck in time' after he is abducted by aliens from the planet Tralfamadore. In a plot-scrambling display of virtuosity, we follow Pilgrim simultaneously through all phases of his life, concentrating on his (and Vonnegut's) shattering experience as an American prisoner of war who witnesses the firebombing of Dresden. Slaughterhouse-Five is not only Vonnegut's most powerful book, it is also as important as any written since 1945. Like Catch-22, it fashions the author's experiences in the Second World War into an eloquent and deeply funny plea against butchery in the service of authority. Slaughterhouse-Five boasts the same imagination, humanity, and gleeful appreciation of the absurd found in Vonnegut's other works, but the book's basis in rock-hard, tragic fact gives it unique poignancy-and humor.

Creative, successful, dyslexic: 23 high achievers share their stories (Jessica Kingsley Publishers, 2016)
Description Not Provided
Foreword by Mollie King , Introduction , David Bailey CBE , Ed Baines , Charley Boorman , Sir Richard Branson , Marcus Brigstocke , Darcey Bussell CBE , Brian Conley , Sophie Conran , Kelly Hoppen MBE , Eddie Izzard , Lynda La Plante CBE , Kenny Logan , Meg Mathews , Nigel McCrery , Steven Naismith , Paul Nixon , Theo Paphitis , Chris Robshaw , Richard Rogers , Sir Jackie Stewart OBE , Zoe Wanamaker CBE , Zelda West-Meads , Benjamin Zephaniah , About dyslexia , Where to go for help.

How to lead: wisdom from the world's greatest CEOs, founders, and game changers (Simon & Schuster, 2020)
"The essential leadership playbook. Learn the principles and guiding philosophies of Bill Gates, Jeff Bezos, Ruth Bader Ginsburg, Warren Buffet, Oprah, and many others through illuminating conversations about their remarkable lives and careers"-- For the past five years, Rubenstein has spoken with the world's highest performing leaders about who they are and how they became successful. Here he distills these revealing conversations into an indispensable leadership guidebook. These agents of change discuss how they got started and how they handle decision making, failure, innovation, change, and crisis. -- adapted from jacket
Introduction , Visionaries. Jeff Bezos ; Bill Gates ; Sir Richard Branson ; Oprah Winfrey ; Warren Buffett , Builders. Phil Knight ; Ken Griffin ; Robert F. Smith ; Jamie Dimon ; Marillyn Hewson , Transformers. Melinda Gates ; Eric Schmidt ; Tim Cook ; Ginni Rometty ; Indra Nooyi , Commanders. President George W. Bush & President Bill Clinton ; General Colin Powell ; General David Petraeus ; Condoleezza Rice ; James A. Baker III , Decision-makers. Representative Nancy Pelosi ; Adam Silver ; Christine Lagarde ; Dr. Anthony S. Fauci ; Justice Ruth Bader Ginsburg , Masters. Jack Nicklaus ; Mike "Coach K" Krzyzewski ; Renée Fleming ; Yo-Yo Ma ; Lorne Michaels.

The Rolling Stone interviews (Back Bay Books, 2007)
Description Not Provided
Introduction , Pete Townsend , Jim Morrison , Phil Spector , John Lennon , Ray Charles , Truman Capote , Johnny Cash , Neil Young , Oriana Fallaci , Brian Wilson , George Lucas , Johnny Carson , Joni Mitchell , Francis Coppola , Tom Wolfe , Jack Nicholson , Bill Murray , Clint Eastwood , Eric Clapton , Tina Turner , Robin Williams , Leonard Bernstein , Spike Lee , Jerry Garcia , Axl Rose , Bruce Springsteen , David Letterman , David Geffen , Kurt Cobain , Courtney Love , Mick Jagger , Patti Smith , Dr. Hunter S. Thompson , Bill Clinton , The Dalai Lama , Bob Dylan , Ozzy Osbourne , Keith Richards , Eminem , Bono.

Talking jazz (W.W. Norton, 1988)
Description Not Provided
1. Clarinet : Paul Barnes, Barney Bigard, Bob Wilber, Edmond Hall, Albert Nicholas , 2. Saxophone : Bud Freeman, Stan Getz, Johnny Griffin, Coleman Hawkins, Johnny Hodges, Gerry Mulligan, Flip Phillips, Zoot Sims, Lucky Thompson, Ben Webster , 3. Brass : Red Allen, Ruby Braff, Buck Clayton, Lee Collins, Harry 'Sweets' Edison, Bobby Hackett, Preston Jackson, Thomas Jefferson, Jonah Jones, Max Kaminsky, Wingy Manone, Jimmy McPartland, Sy Oliver, Jim Robinson and Kid Howard , 4. Rhythm section : Piano: Mary Lou Williams, Joe Bushkin, Hoagy Carmichael ; Guitar: Eddie Condon ; Bass: Joe Benjamin, Slam Stewart , 5. Singers: Billy Eckstine, Billie Holiday, Sarah Vaughan, Dinah Washington.

Gene Roddenberry: the last conversation (Portraits of American genius, 2,, 1994)
Description Not Provided

Master photographers: the world's great photographers on their art and technique (C.N. Potter, 1983)
Description Not Provided
Ansel Adams , Eve Arnold , David Bailey , Bill Brandt , Harry Callahan , Louise Dahl-Wolfe , Robert Doisneau , Elliott Erwitt , Ralph Gibson , Horst , Yousuf Karsh , Andre Kertesz , Jacques-Henri Lartigue , Sarah Moon , Arnold Newman , Helmut Newton

Gene Roddenberry: the last conversation : a dialogue with the creator of Star Trek (Pocket Books, 1996)
Description Not Provided